Medical Intervention Alone vs Surgical Drainage for Treatment of Peritonsillar Abscess: A Systematic Review and Meta‐analysis. (2nd June 2020) - Forner, David; Curry, Dennis E.; Hancock, Kristy; MacKay, Colin; Taylor, S. Mark; Corsten, Martin; Trites, Jonathan R.; Rigby, Matthew H.
Abstract : Objective: Peritonsillar abscesses (PTAs) are common emergency consultations for otolaryngologists. Medical management alone may offer satisfactory treatment without the risk associated with surgical drainage. Therefore, we performed a systematic review of medical treatment alone compared to surgical drainage for the treatment of PTA. Data Sources: MEDLINE, EMBASE, Cochrane CENTRAL, and ClinicalTrials.gov. Review Methods: Studies comparing the outcomes of medically treated to surgically treated patients were included. Risk of bias was assessed using the Newcastle‐Ottawa Scale. All screening and data extraction were completed by 2 independent reviewers. Meta‐analysis was performed using a random‐effects model. Subgroup and sensitivity analyses were performed. Results: Ten cohort studies and 2 randomized studies were included (ntotal = 33, 468). Study quality was low, with only 1 study providing multivariable analysis. The combined rate of treatment failure in patients initially treated with medical management alone was 5.7% compared to 5.5% in the surgical group. There was no statistically significant difference in the odds of treatment failure between interventions through random‐effects meta‐analysis (odds ratio [OR], 1.10; 95% CI, 0.53‐2.26; I 2 = 41%; P =. 13). Subgroup analysis excluding pediatric‐specific studies revealed similar odds of treatment failure when initially managed with medical intervention (OR, 0.92; 95% CI, 0.56‐1.50; P =. 39; I 2 = 0%). Conclusion: Meta‐analysis of available studies demonstrated no difference in odds of treatment failure for patients with PTA managed through medical intervention alone compared to surgical intervention. These findings should be interpreted with caution due to high probability of bias and overall low quality of studies.